2010
DOI: 10.1103/physrevc.81.064315
|View full text |Cite
|
Sign up to set email alerts
|

Role of ground-state correlations in hypernuclear nonmesonic weak decay

Abstract: The contribution of ground state correlations (GSC) to the non-mesonic weak decay of 12 Λ C and other medium to heavy hypernuclei is studied within a nuclear matter formalism implemented in a local density approximation. We adopt a weak transition potential including the exchange * Electronic address:

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
51
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 50 publications
(71 reference statements)
9
51
0
Order By: Relevance
“…In the evaluation of Γ N M , and the corresponding spectra, are used the Shell Model (SM) and the Fermi Gas Model (FGM) for Γ 1 (within the two-particle phase space) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][20][21][22][23], while for Γ 2 (within the three-particle phase space) only the later model has been employed so far [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In the evaluation of Γ N M , and the corresponding spectra, are used the Shell Model (SM) and the Fermi Gas Model (FGM) for Γ 1 (within the two-particle phase space) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][20][21][22][23], while for Γ 2 (within the three-particle phase space) only the later model has been employed so far [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the nuclear recoil is also taken into account as a new feature of our approach, which is applied to 12 Λ C. Formally, this corresponds to implement translational invariance and exact momentum conservation in the nonmesonic decays. The same microscopic approach showed that ground state correlation contributions are crucial for a detailed calculation of the rates, the asymmetry parameter and the nucleon emission spectra [19,20,22,24]. Less pronounced effects were reported by including the ∆-baryon resonance [23].…”
mentioning
confidence: 98%
“…One should keep in mind that, by definition, the decay widths cannot contain any (final state) interaction among the weak decay nucleons [20]. Nevertheless, in our approach the strong nucleon-nucleon interaction, V N N , plays a role in the definition of the hypernuclear ground state, which, using perturbation theory up to second order in V N N , reads:…”
mentioning
confidence: 99%
See 2 more Smart Citations